2000
DOI: 10.1002/1097-4628(20000801)77:5<955::aid-app2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

New hydrogel containing sulfur compound prepared by ? irradiation and its application for metal recovery

Abstract: A new hydrogel that contains sulfur is prepared by radiation polymerization and its application for recovery of Hg2+, Pb2+, Cd2+, and Cu2+ ions is discussed. The metal hydrogel complexes are isolated and characterized by using different spectroscopic techniques (UV‐visible, IR, NMR, and mass), thermal analysis (TGA and DSC) measurements, and SEM. Also, the mode of complexation is determined using IR and NMR spectroscopy. The scanning electron micrographs show that the hydrogel has a great ability to recover th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…On the other hand, the data obtained corresponding to reactive dye (Figure 12) shows a lower affinity than that of the basic dye (Figure 11). The reactive dye used is of the halogen substitution type and it would be expected that its labile chlorine atoms react with the already existing hydroxyl groups of the cellulose structure 10…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the data obtained corresponding to reactive dye (Figure 12) shows a lower affinity than that of the basic dye (Figure 11). The reactive dye used is of the halogen substitution type and it would be expected that its labile chlorine atoms react with the already existing hydroxyl groups of the cellulose structure 10…”
Section: Resultsmentioning
confidence: 99%
“…A sample of known weight (0.5 mg) of the modified fabric was then immersed in these solutions for different time intervals ranging from 1 h to 24 h. The residual metal solution was measured by UV spectrophotometer. The metal uptake (%) was carried out in a batch process and determined using 10 mL of metal ions solution as following equation10: where C o and C 1 are the initial and residual concentrations of metal ions solution (ppm), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage metal sorption by the AAc/MBI hydrogel was determined by a complexometric method described in detail in a previous study 15…”
Section: Methodsmentioning
confidence: 99%
“…Radiation polymerization studies on preparing hydrogels include the mechanism of reaction, kinetics, and structure 11–14. In previous work, the preparation of a hydrogel based on acrylic acid and trithioglycolic acid by radiation polymerization, and its application in the recovery of metal ions, was reported 15. It was found that the solvent mixture is a determining factor affecting the gel fraction and water absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is one of our interests to prepare hydrogels under the effect of gamma radiation and to investigate their application in the removal of toxic pollutants. In this regard, hydrogels based essentially on polyacrylic (PAAc) acid with trithioglycolic acid or 2‐mercaptobenzimidazole were recently synthesized by gamma radiation crosslinking and applied in the recovery of Hg 2+ , Pb 2+ , and Cu 2+ ions 8, 9…”
Section: Introductionmentioning
confidence: 99%